2018
DOI: 10.1037/ebs0000111
|View full text |Cite
|
Sign up to set email alerts
|

The evolved classroom: Using evolutionary theory to inform elementary pedagogy.

Abstract: Because the goal of education is to provide children with the skills needed to succeed later in life, it should come as no surprise that there is seemingly unending dispute about how best to educate our children. From an evolutionary perspective, the current system of education in the United States may be seen as highly unnatural and mismatched with the evolutionary history of our species. For example, rather than learning in mixed-age playgroups, children now find themselves in compulsory age-segregated class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Differences in the educational consequences of early education as a function of the degree to which teachers provide children with evolutionary-relevant experiences was illustrated in a study in which college students related their enjoyment and academic success in school to the number of evolutionary-relevant experiences they recalled having in kindergarten through second grade (Gruskin & Geher, 2018; see Table 1). The researchers reported that the more evolutionary-relevant early school experiences (e.g., free play, real-world applications for learning, hands-on learning) the participants had had, the more they enjoyed elementary, middle, and high school, and the higher was their high-school grade-point average (GPA).…”
Section: Developmentally Appropriate Practices Are Evolutionarily App...mentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in the educational consequences of early education as a function of the degree to which teachers provide children with evolutionary-relevant experiences was illustrated in a study in which college students related their enjoyment and academic success in school to the number of evolutionary-relevant experiences they recalled having in kindergarten through second grade (Gruskin & Geher, 2018; see Table 1). The researchers reported that the more evolutionary-relevant early school experiences (e.g., free play, real-world applications for learning, hands-on learning) the participants had had, the more they enjoyed elementary, middle, and high school, and the higher was their high-school grade-point average (GPA).…”
Section: Developmentally Appropriate Practices Are Evolutionarily App...mentioning
confidence: 99%
“…Originally, developmentally appropriate practice stemmed from Piaget's theory of cognitive development, recognizing that young children are qualitatively different thinkers and learners than older children. Although not based on evolutionary theory, developmentally appropriate practice involves many components that can be described Gruskin, K., & Geher, G. (2018). The evolved classroom: using evolutionary theory to inform elementary pedagogy.…”
Section: Developmentally Appropriate Practices Are Evolutionarily App...mentioning
confidence: 99%
“…It is not surprising that there is a visible debate about how to educate our children in the most efficient and appropriate manner [3]. In comparison to the evolutionary history of people and their learning process, the current educational system is exceedingly unnatural and confused [4]. From an academic institution's front entrance to its grounds and classrooms, every aspect of the built environment of a learning space influences brain processing and has a direct impact on how students feel and experience while they are in that area.…”
Section: Introductionmentioning
confidence: 99%